New method for measuring thickness in thin transparent medium - Sousa, Raul A. R. C. (2011)
The aim of this method is to determine the thickness of a transparent medium, close to the corneal thickness, using the angle at the first and second Purkinje images are aligned for a specific optical slit width. An optical slit is projected in an oblique angle relatively to the transparent medium, producing two different reflections in each medium surface (first and second Purkinje images). The slit is then moved until the first and second Purkinje images of the slit are aligned in such a way, that look as if they were a continuous slit. The slit width, the angle between the illumination and observation, and the medium index are used, then, to calculate the medium thickness. This method was implemented in a slit lamp and the central thicknesses (CT) of nine gas-permeable contact lenses (CL) were measured, with this method and a mechanical gauge and the results were compared. The mean CT difference ± standard deviation, between the two methods was 0.004 ± 0.008 mm with minimum and maximum absolute values of 0.002 and 0.019 mm. This technique showed good precision to measure the CT of CL and should be tried in human corneas.